The empirics of financial inclusion in the Philippines - Alinsunurin, Maria Kristina Galvez (Animo Repository, 2011)
Financial inclusion’s association with economic growth and development has been widely established in the literature. While wide variations of financial inclusiveness among economies persist, basic indicators in the Philippines do not fully relate financial inclusion with household characteristics. Our paper innovates on this research gap and as such contributes to the literature by describing inclusion at the household level. We model financial inclusion in terms of households’ borrowing access to informal, formal and mixed sources. Utilizing the latest round of the Philippines’ Annual Poverty Indicators Survey (2013), our estimates reveal that the odds of borrowing from formal sources is 19.1% less likely for households belonging to the lowest income quintile; households with PhilHealth membership show 49.5% odds in engaging in formal borrowing. Our work emphasizes that policy makers should take into account household-level characteristics in designing policies that should foster deeper and wide access to financial services.